Efektivitas Media Sosial Instagram Dalam Publikasi HUT Museum Nasional Indonesia (MNI) Kepada Masyarakat - Silvina Mayasari; Clavinda Indraswari (Universitas Bina Sarana Informatika, 2018)
Abstract - The museum is a place for permanent exhibition of objects that deserve public attention, such as historical heritage, art, and science; a place to store antiquities; to show the public for the needs of study, education and pleasure. But in this day and age the museum is only considered as a place to store antic and old-fashioned things, a lack of interest in the community to make the museum as a place of visit in adding insight and knowledge.The lack of publications and information about the museum is also a factor in the community's lack of interest in the museum. The Indonesian National Museum held its 240th Anniversary event on April 21, 2018 to April 29, 2018, by publishing these activities through Instagram social media, because of the pattern of people today who use Instagram more. Where the National Instagram Museum informs about what activities are on the 240th Anniversary of MNI so that more Indonesian people know and are interested in attending the event.